ANALISIS PROBLEMATIKA PEMBELAJARAN MATEMATIKA DI SMP SWASTA PEDESAAN - Kumening, Ayu Sulistya; Ramadhani, Luthfiasari; Putranto, Sumbaji (Dharmas Education Journal (DE_Journal), 2023)
Problems in learning mathematics are found at every level of education, for this reason special attention is needed and solutions are provided so that they cannot interfere with mathematics learning activities. The purpose of this study was to analyze the problems that occur in learning mathematics in rural private junior high schools. The focus in this research is to analyze the problems that come from teachers and students during the mathematics learning process. This research use descriptive qualitative approach. Data collection techniques were carried out by interviews, observation, and documentation. The data analysis used is to describe the results of observations and interviews with mathematics teachers at schools. The results showed that the problems of learning mathematics in rural private junior high schools included the lack of interest and motivation of students towards learning mathematics, students not focusing on participating in mathematics learning activities, the low ability of teachers in class management, and the lack of ability of teachers to increase student motivation.